Hipertrofia adenotonsilar em crianças com doença falciforme - Gois, Carlos Rodolfo Tavares de (2016)
Adenotonsillar hypertrophy (ATH) seems to be more frequent and persistent in children with sickle cell disease (SCD), which causes a negative impact since it increases the recurrence of pharyngitis and leads to sleep-disordered breathing (SDB), thus increasing the risk of polymerization of hemoglobin S and thereby vaso-occlusive crisis and other complications. The objectives of the study were to determine the frequency of ATH in preschool children with SCD; observe whether there is an association between ATH and age within the age group studied, assess whether the subscale of SDB is associated with the diagnosis of ATH in preschool children with or without SCD and correlate the presence of ATH with features and clinical complications in preschool children with SCD. It is an analytical observational study, consisting of a study group composed of 48 children with SCD and a control group of 35 children without such disease. All children underwent oropharyngoscopy with front light and nasal video endoscopy, while parents and / or guardians answered the questions of SDB subscale of the Sleep Disturbance Scale for Children (SDSC). The presence of ATH was considered when palatine tonsils were grades three or four of Brodsky scale (1989) and / or when pharyngeal tonsil occluded choanaes in at least 70% (1st criterion) or 50% (2nd criterion). In children with SCD were also surveyed on records the following characteristics and clinical complications of SCD: level of hemoglobin F (HbF), child's age when they began presenting specific symptoms of SDC, history of transfusions and hospitalizations due to painful crises, cerebrovascular accident (CVA) and acute chest syndrome (ACS). Twelve children from the study group (25%) and eight children in the control group (20%) had ATH when we used the 1st criterion of obstruction by the pharyngeal tonsil. When used the 2nd criterion, 18 (37.5%) children in the study group and 13 (37.1%) children in the control group received this diagnosis, with no significant difference between the frequencies in both groups regardless of the obstruction criteria used (p = 0.246 and p = 0.061, respectively). There was only association between ATH and age in the control group and only when the 1st criterion of obstruction by the pharyngeal tonsil was used (p = 0.043). The SDB subscale of EDSC joined the diagnosis of ATH regardless of pharyngeal obstruction criteria used both in the study group (p = 0.0025 for 1st criterion and p = 0.008 for the 2nd), as in the control group (p = 0.0026 for 1st criterion and p = 0.0018 for 2nd). Among the features and clinical complications of SDC, the ATH showed a correlation only with a higher percentage of HbF. It was concluded that ATH was not associated with SDC in preschool children in the study sample; the age of five years was the most affected by ATH in children without the diagnosis of SDC, when used 1st criterion of pharyngeal obstruction; the SDB subscale of SDSC presented itself as a useful tool for the suspected diagnosis of ATH in preschool children with or without SDC; ATH was associated with a higher percentage of HbF in children with SCD.